2020
DOI: 10.1111/tbj.13812
|View full text |Cite
|
Sign up to set email alerts
|

Acute toxicities after proton beam therapy following breast‐conserving surgery for breast cancer: Multi‐institutional prospective PCG registry analysis

Abstract: Radiotherapy (RT) after breast-conserving surgery (BCS) for breast cancer improves breast cancer mortality and decreases recurrence. 1 However, the benefit of adjuvant breast RT is partially offset by nonbreast morbidity caused by dose to normal structures, including the heart. 2 Various techniques and technologies are used to minimize the dose to surrounding normal structures including deep inspiration breath-hold, intensity-modulated radiation therapy, and proton beam therapy (PBT). 3 Adjuvant whole-breast R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…In the present study, we report favorable LRFS and OS following re-irradiation for locoregional recurrent breast cancer, similar to other cohorts [7,14,15,17,19,20,27]. Particularly, high rates of disease control were seen among curative intent patients undergoing complete surgical excision followed Proton therapy for breast cancer offers enhanced ability to spare non-target tissue, including the heart and lungs [24,[28][29][30][31][32][33], which is of particular importance and interest for re-irradiation. Reirradiation with PBT has been reported in multiple disease sites, including in CNS, head and neck, gynecological, gastrointestinal, and lung tumors [34][35][36][37][38][39][40][41].…”
Section: Discussionsupporting
confidence: 80%
“…In the present study, we report favorable LRFS and OS following re-irradiation for locoregional recurrent breast cancer, similar to other cohorts [7,14,15,17,19,20,27]. Particularly, high rates of disease control were seen among curative intent patients undergoing complete surgical excision followed Proton therapy for breast cancer offers enhanced ability to spare non-target tissue, including the heart and lungs [24,[28][29][30][31][32][33], which is of particular importance and interest for re-irradiation. Reirradiation with PBT has been reported in multiple disease sites, including in CNS, head and neck, gynecological, gastrointestinal, and lung tumors [34][35][36][37][38][39][40][41].…”
Section: Discussionsupporting
confidence: 80%
“…In comparison to non-PBS, PBS has the advantage of skin dose-sparing [ 7 8 ]. Table 5 displays the incidences of grade 2–3 dermatitis after PBT [ 3 4 5 23 24 25 26 27 28 29 30 31 32 33 34 ]. In patients who received conventional fractionated PBT without PBS, the rates of grade 2–3 dermatitis ranged from 71% to 100% (median, 82%).…”
Section: Discussionmentioning
confidence: 99%
“…Higher BMI has been shown to be associated with worse quality of life in other cancers [ 22 , 23 ]. Similarly, higher BMI has also been shown to correlate to worse physician reported adverse events [ 24 , 25 ]. In a study of breast cancer survivors, Anbari et al used the validated 36-Item Short Form Health Survey to compare quality of life to changes in BMI which showed that a BMI change corresponded to 5 of the 8 domains [ 26 ].…”
Section: Discussionmentioning
confidence: 99%